2001
DOI: 10.1289/ehp.01109973
|View full text |Cite
|
Sign up to set email alerts
|

Multiple metal contamination from house paints: consequences of power sanding and paint scraping in New Orleans.

Abstract: Power sanding exterior paint is a common practice during repainting of old houses in New Orleans, Louisiana, that triggers lead poisoning and releases more than Pb. In this study we quantified the Pb, zinc, cadmium, manganese, nickel, copper, cobalt, chromium, and vanadium in exterior paint samples collected from New Orleans homes (n = 31). We used interior dust wipes to compare two exterior house-painting projects. House 1 was measured in response to the plight of a family after a paint contractor power sande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 20 publications
(13 reference statements)
3
45
0
Order By: Relevance
“…These 250 results are consistent with the findings of previous studies of Pb based paint 26,27 . This particle also contains a distinctive Fe-Zn dominated phase that runs directly across its surface.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These 250 results are consistent with the findings of previous studies of Pb based paint 26,27 . This particle also contains a distinctive Fe-Zn dominated phase that runs directly across its surface.…”
Section: Discussionsupporting
confidence: 90%
“…In all these particles C, Si, Zn, Fe, Ca are common components together with Ba, Ni, Pb, Cu, Mn and Ti. With the exception of relatively low S concentrations, this elemental profile is consistent with ZnS paints 26,27 , including 245 radioluminescent paints. Such paints frequently contained Cu, Mn and other additives to alter their colour, luminescence, stability and viscosity and flow properties.…”
Section: Discussionsupporting
confidence: 69%
“…Mielke et al, 2001;Mielke et al, 2010;Mielke et al, 2011;Taylor et al, 2013;Taylor et al, 2014). A survey (Thornton et al, 1990) of metals in UK dusts has shown that most of the dusts collected from urban environments had widespread Pb contamination ranging from 172 to 9600 mg/kg; other studies have reported (Wang et al, 2006) that for example in China, 80% of children exposed to urban dust had an excessive blood lead level.…”
Section: Introductionmentioning
confidence: 99%
“…The dust lead levels declined to less than the detection limit (3 µg/ft 2 ) and remain low (Mielke 2001). However, the attic, the yard, the layers of lead-dust next to the playhouse, and a room used for decontamination purposes remain to be cleaned.…”
mentioning
confidence: 99%
“…The concentration of lead in the paint on the exterior power-sanded surface averaged 130,000 ppm (Mielke et al 2001). The federal definition of lead-based paint in housing is 5,000 ppm (Residential Lead-Based Paint Hazard Reduction Act 1992).…”
mentioning
confidence: 99%